Atividades didáticas integradas: ensino de língua portuguesa em perspectiva interdisciplinar - PAIXÃO, Ivaneide da Silva (Universidade Federal do Oeste do Pará, 2024)
This research, under the title Integrated Didactic Activity: Teaching Portuguese Language in an Interdisciplinary Perspective, was structured and carried out in accordance with the requirements of the Professional Master's Program in Literature – PROFLETRAS. Discusses the teaching of the Portuguese Language based on Integrated Didactic Activities (ADIs) – created by Moura (2017), informed by principles of Bakhtin's Theory and using speech genres as a teaching object. The reflections carried out on language teaching from an interdisciplinary, dialogical, socio-cognitive, interactive and reflective perspective emphasize the use of discursive genres and the amalgam of elements that add to make the knowledge learned/constructed at school go beyond the context of the classroom. class and apply to students’ experiences. In the construct, data and evidence that point to the contributions of Integrated Didactic Activities to the teaching-learning process as a tool for organizing pedagogical work, teaching methodology and an instrument for change in the face of real everyday contexts. The analyzed corpus was obtained through the collection of data produced during the implementation of the Intervention Project “Here we are, ...”, whose actions were developed with 6th and 7th year students from the Artur Municipal School of Early Childhood and Elementary Education. Pessoa, a teaching unit in the rural area of the municipality of Altamira-PA – a fact that gives the research, in terms of procedures, the characteristic of participant. The discussion is based primarily on Bakhtin's theory (1981, 2010) and the studies of other researchers such as Marcuschi (2007), Kleiman (2002), Koch and Elias (2010), Rojo (2002), Antunes (2003), Geraldi (1997, 1995, 2010) and Moura (2021, 2018, 2017) who, like Bakhtin, consider language a cognitive, social and historical activity, and help in understanding and carrying out Integrated Didactic Activities. The research presented the following results: Integrated Didactic Activities attribute dynamism and flexibility to the organization of pedagogical work, enhance language teaching by favoring the expansion of students' linguistic and discursive capabilities, modify the way of acting and thinking about the teaching-learning process and life. This result extended to the perspectives of the study's contribution and proved to be powerful in the formation of more responsive and independent subjects, in interdisciplinary teaching-learning, in the production of knowledge based on the social reality in which we live.